PENGARUH KOMUNIKASI PIMPINAN TERHADAP SEMANGAT KERJA STAFF MARKETING PADA PT. SINARMAS MULTIFINANCE CABANG PEKANBARU - Reza Maulana; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
According to the human relations theory pioneered by Bernard (1938), Mayo (1933), Roethlishetger, and Dicshon (1939), this theory suggested organizational refinement and improvement strategies by increasing satisfaction of member organizations and create an organization that can help individuals develop its potential. To avoid this need to have a way that can create a harmonious labor relations, mutually beneficial cooperation and mutual understanding that ultimately all parties can get satisfaction together. Communication is carried out by the leadership against subordinates certainly has an important role in creating a harmonious labor relations, mutually beneficial cooperation and mutual understanding so that all parties can get satisfaction together. The purpose of this research is to find out how big the influence of communication leadership against the marketing staff morale at PT. Sinarmas Multifinance branch Pekanbaru.The methods used in this study i.e., quantitative methods. Data collection techniques in the study using a detailed questionnaire. The number of samples to study as many as 40 of the respondents. Withdrawal of samples using the method of census sampling or saturated. To know the influence of both these variables, the researchers used a simple linear regression analysis. For the processing of data is carried out using a questionnaire, the statistical program Product And Service Solution (SPSS) Windows version 18.The results of the research on the influence of communication leadership against the marketing staff morale at PT. Sinarmas branch Multifinance Pekanbaru obtained coefficients regression on this research is Y = 12.618 + 0.567 X with significance level smaller than 0.000 α = 0.05. This means that there is a leader of communication influence against the marketing staff morale at PT. Sinarmas branch Multifinance Pekanbaru of 49.70% and enter influencial medium category. The percentage shows that communication conducted the leadership is quite effective to improve the morale of employees. H0 is rejected and thus Ha is received.Keywords : Communication, Leadership, Morale